Transcranial magnetic stimulation of the precuneus enhances memory and neural activity in prodromal Alzheimer's disease - Koch, Giacomo; Bonnì, Sonia; Pellicciari, Maria Concetta; Casula, Elias P.; Mancini, Matteo; Esposito, Romina; Ponzo, Viviana; Picazio, Silvia; Di Lorenzo, Francesco; Serra, Laura; Motta, Caterina; Maiella, Michele; et al. (NeuroImage (Orlando, Fla.), 2018)
Memory loss is one of the first symptoms of typical Alzheimer's disease (AD), for which there are no effective therapies available. The precuneus (PC) has been recently emphasized as a key area for the memory impairment observed in early AD, likely due to disconnection mechanisms within large-scale networks such as the default mode network (DMN). Using a multimodal approach we investigated in a two-week, randomized, sham-controlled, double-blinded trial the effects of high-frequency repetitive transcranial magnetic stimulation (rTMS) of the PC on cognition, as measured by the Alzheimer Disease Cooperative Study Preclinical Alzheimer Cognitive Composite in 14 patients with early AD (7 females). TMS combined with electroencephalography (TMS-EEG) was used to detect changes in brain connectivity. We found that rTMS of the PC induced a selective improvement in episodic memory, but not in other cognitive domains. Analysis of TMS-EEG signal revealed an increase of neural activity in patients' PC, an enhancement of brain oscillations in the beta band and a modification of functional connections between the PC and medial frontal areas within the DMN. Our findings show that high-frequency rTMS of the PC is a promising, non-invasive treatment for memory dysfunction in patients at early stages of AD. This clinical improvement is accompanied by modulation of brain connectivity, consistently with the pathophysiological model of brain disconnection in AD. •The precuneus is a key area for memory impairment in Alzheimer’s disease (AD).•We investigated the effects of precuneus-rTMS on memory in patients with early AD.•Precuneus-rTMS induced a selective improvement in episodic memory.•Precuneus-rTMS enhance precuneus activity and connectivity with frontal areas.•Precuneus-rTMS is a promising treatment for memory dysfunction in early AD patients.